Coordenação pedagógica na educação infantil: trabalho e identidade de profissional na rede municipal de ensino de Goiânia - LIMA, Nancy Nonato de (2007)
Our research composes one of various subprojects on development in the project Public Politics and Childhood Education in Goiás: history, conceptions, projects and practical, of the Studies and Researches of Childhood Education group, on the research line Teaching Formation and Professionalization for the concession of the doctor s degree on the research program of the Education Faculty, in the Federal University of Goiás. We investigate the pedagogical coordination at the childhood education, trying to understand the work and the constitution of the professional identities of the pedagogical coordinators on the Municipal Centers of Childhood Education in Goiânia. We adopt the principle that the pedagogical coordination is one dimension in the administration, responsible for the collective joint of pedagogical and political project as well as of learning and teaching process, on a democratic perspective. On the basis of dialectical materialist method, we developed one theoretical research, documental and empirical, with the participation of ninety and three pedagogical coordinators, on seventy and six childhood educational centers, in the years of 2005 and 2006. The investigative data construction articulates documents analysis, questionnaires and interviews. Aiming at to catch the concrete and contradictory movement of the research object on the social and historical totality, we realized analysis and critical reflections on a dialogue with Marx, Mészáros, Frigotto, Mascarenhas, Kuenzer; in educational administration area: Dourado, Paro, Silva Jr., Oliveira, D.; on the childhood education field: Barbosa, Oliveira, Z., Rosemberg, Arce, Faria; about the educator s formation course: Brzezinski, Freitas, H., Anfope. We identify challenges, commitments and not commitments, possible advanced for the childhood education as a field of public politics, to understand the material and symbolical conditions that mediates the pedagogical work in this educational stage. We analyze the history and actual proposes for scholar administration of the educational municipal system and we evidence limits and possibilities, around the democratic administration, that we understand as a necessary utopy on the fight for social quality on education, in opposition to the total quality desired for the market. We perceive the complexity, the challenges and the ambiguous aspect of the coordination work on the educational childhood centers, where the professional identities construction happens on the social production process and incorporates collective and individual aspects in the images and self images historically transformed of the teaching work, the educator s formation courses identity, school supervision, educational childhood institutions, child and childhood. Catching the contradiction of the real is possible to affirm that the pedagogical coordinators play an important role on the childhood centers administration, being able to contribute for a democratic and collective administration on the childhood education, in the historical limits of the social materiality